Implementing urban agriculture as nature-based solutions in China: Challenges and global lessons - Zhe Zhu; Faith Ka Shun Chan; Gang Li; Mengxia Xu; Meili Feng; Yong-Guan Zhu (Elsevier, 2024)
Urban agriculture, the cultivation, processing and distribution of plants and animals within urban or suburban boundaries, is becoming an increasingly relevant strategy to enhance food safety for urban residents. With the rapid urbanization in the past decades, three forms of urban agriculture have emerged in China: small-scale, capital-intensive, and tourism-type. Each form presents unique benefits and challenges, and their development has been largely shaped by the local socio-economic context and government policies. The benefits of urban agriculture are numerous including the improvement of community cohesion, promotion of physical health, enhancement of environmental sustainability, and creation of new economic opportunities. However, it also faces many challenges such as land availability, capital shortage, market access, and governmental support. This review summarized the benefits of urban agriculture and its current limitations and challenges, and proposed strategies to overcome these hurdles in China based on successful examples in the Global North. Four specific recommendations were provided to promote urban agriculture in China: integration of urban agriculture into cities, solutions for land and resource use, government support and actions, as well as planning and regulations. Adoption of these recommendations is expected to result in healthier cities and a more robust agricultural system in China.